Reply to the comment on: “Dalbavancin for infective endocarditis: a systematic review of effectiveness, safety, and dosing” - Anastasios E Chaldoupis; Vasilios Petrakis; Petros Ioannou; Konstantina A Tsante; Deny Tsakri; Aglaia Domouchtsidou; Stella Baliou; Marianna Vlachaki; Alexandra Mpakosi; Sotirios P Fortis; George Samonis; Rozeta Sokou; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Dalbavancin for infective endocarditis: A systematic review of effectiveness, safety, and dosing - Anastasios E Chaldoupis; Vasilios Petrakis; Petros Ioannou; Konstantina A Tsante; Deny Tsakri; Aglaia Domouchtsidou; Stella Baliou; Marianna Vlachaki; Alexandra Mpakosi; Sotirios P Fortis; George Samonis; Rozeta Sokou; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2026)
Purpose Infective endocarditis (IE) requires prolonged intravenous antibiotic therapy, leading to extended hospitalization and increased morbidity. Dalbavancin, a long-acting antibiotic with excellent tissue penetration and a favorable safety profile, can be a promising alternative. This systematic review aimed to investigate the current literature regarding the use of dalbavancin for infective endocarditis. Methods A systematic search of PubMed and Scopus was conducted according to PRISMA guidelines. Eligible studies included adult patients (≥ 18 years) with IE diagnosed by the modified Duke criteria, treated with dalbavancin as monotherapy or sequential/consolidation therapy. Data extraction included demographics, type of IE, causative pathogen, dosing regimen, surgical intervention, adverse events, and outcomes. Descriptive analyses were performed. Results Thirty-eight studies including 565 patients were analyzed. The overall cure rate was 88.0%, with a similar success rate across native valve (90.1%), prosthetic valve (90.0%), and cardiac device-related IE (86.0%). Staphylococcus aureus , Coagulase-negative staphylococci (CNS), Streptococcus spp ., and Enterococcus faecalis were the most common pathogens. Cure rates were comparable among most pathogens, though a lower cure rate was evident in infections due to Enterococcus faecalis compared to Streptococcus spp. (80.7% vs. 96.6%, p = 0.008). An effective antimicrobial exposure of 2 weeks had similar success rate compared to a longer period of effective antimicrobial exposure ( p = 0.31). Adverse events were rare (2.9%), with mild rash being the most common. Conclusions Dalbavancin demonstrates high cure rates and excellent tolerability in IE, and could offer an attractive alternative to conventional prolonged intravenous therapy. Further randomized controlled trials are warranted to define standardized protocols.

Trends of isolation of intrinsically resistant to colistin Enterobacteriaceae and association with colistin use in a tertiary hospital - G. Samonis; I. P. Korbila; S. Maraki; I. Michailidou; K. Z. Vardakas; D. Kofteridis; D. Dimopoulou; V. K. Gkogkozotou; M. E. Falagas (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Antimicrobial activity of prulifloxacin in comparison with other fluoroquinolones against community-acquired urinary and respiratory pathogens isolated in Greece - D. E. Karageorgopoulos; S. Maraki; A. C. Vatopoulos; G. Samonis; G. C. Schito; M. E. Falagas (European Journal of Clinical Microbiology & Infectious Diseases, 2013)

Antimicrobial susceptibility of non-fermenting Gram-negative isolates to isepamicin in a region with high antibiotic resistance - G. Samonis; S. Maraki; E. K. Vouloumanou; G. G. Georgantzi; D. P. Kofteridis; M. E. Falagas (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Long-term trends in the epidemiology and resistance of childhood bacterial enteropathogens in Crete - S. Maraki; F. Ladomenou; G. Samonis; E. Galanakis (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Empirical therapy with ceftazidime combined with levofloxacin or once-daily amikacin for febrile neutropenia in patients with neoplasia: a prospective comparative study - G. Samonis; E. Koutsounaki; D. E. Karageorgopoulos; P. Mitsikostas; C. Kalpadaki; V. Bozionelou; I. Bompolaki; J. Sgouros; V. Taktikou; M. E. Falagas (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Synergy of fosfomycin with carbapenems, colistin, netilmicin, and tigecycline against multidrug-resistant Klebsiella pneumoniae, Escherichia coli, and Pseudomonas aeruginosa clinical isolates - G. Samonis; S. Maraki; D. E. Karageorgopoulos; E. K. Vouloumanou; M. E. Falagas (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Multi-drug-resistant gram-negative bacterial infection in surgical patients hospitalized in the ICU: a cohort study - V. G. Alexiou; A. Michalopoulos; G. C. Makris; G. Peppas; G. Samonis; M. E. Falagas (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Infant colonization by Staphylococcus aureus: role of maternal carriage - E. Chatzakis; E. Scoulica; N. Papageorgiou; S. Maraki; G. Samonis; E. Galanakis (European Journal of Clinical Microbiology & Infectious Diseases, 2011)

Serratia infections in a general hospital: characteristics and outcomes - G. Samonis; E. K. Vouloumanou; M. Christofaki; D. Dimopoulou; S. Maraki; E. Triantafyllou; D. P. Kofteridis; M. E. Falagas (European Journal of Clinical Microbiology & Infectious Diseases, 2011)

Serotypes and susceptibilities of paediatric clinical isolates of Streptococcus pneumoniae in Crete, Greece, before and after the heptavalent pneumococcal conjugate vaccine - S. Maraki; G. Samonis; E. Galanakis (European Journal of Clinical Microbiology & Infectious Diseases, 2010)

Citrobacter infections in a general hospital: characteristics and outcomes - G. Samonis; D. E. Karageorgopoulos; D. P. Kofteridis; D. K. Matthaiou; V. Sidiropoulou; S. Maraki; M. E. Falagas (European Journal of Clinical Microbiology & Infectious Diseases, 2009)

Candidemia in immunocompromised and immunocompetent critically ill patients: a prospective comparative study - G. Dimopoulos; A. Karabinis; G. Samonis; M. E. Falagas (European Journal of Clinical Microbiology & Infectious Diseases, 2007)

Effectiveness and nephrotoxicity of intravenous colistin for treatment of patients with infections due to polymyxin-only-susceptible (POS) gram-negative bacteria - M. E. Falagas; S. K. Kasiakou; D. P. Kofteridis; G. Roditakis; G. Samonis (European Journal of Clinical Microbiology & Infectious Diseases, 2006)

Serotype distribution and antimicrobial resistance of Salmonella enterica from patients with gastroenteritis in Crete, Greece - S. Maraki; G. Samonis; E. Mantadakis; E. Nioti; Y. Tselentis (European Journal of Clinical Microbiology & Infectious Diseases, 2006)

Antimicrobial resistance of Streptococcus pneumoniae isolates in Athens, Greece - S. Kanavaki; E. Mantadakis; S. Karabela; M. Anatoliotaki; M. Makarona; H. Moraitou; A. Pefanis; G. Samonis (European Journal of Clinical Microbiology & Infectious Diseases, 2005)